Utilization of Social Capital in the Production and Distribution of Dodol Business in Tanjung Pura, Langkat Regency - Zahri Nura; Amiruddin Ketaren; Rakhmadsyah P Rangkuty; Nulwita Maliati; Suadi Zainal; Muhammad Bin Abubakar (Program Magister Administrasi Publik, 2025)
This research aims to understand how the social capital of Tanjung Pura dodol craftsmen is utilized in the production and distribution of dodol and the efforts of dodol craftsmen and traders in maintaining the dodol business. This research uses social capital theory according to Putnam. The research method uses qualitative methods with data collection techniques, namely observation, interviews and documentation. The results of this research show that the use of social capital of Tanjung Pura dodol craftsmen in the production and distribution of dodol is (a) dodol craftsmen build networks in obtaining raw materials by collaborating with raw material suppliers. This cooperative relationship is based on trust and there are agreed rules for working together, (b) dodol craftsmen build a collaborative network with traders and distributors in marketing dodol. This cooperative relationship is based on trust and mutually agreed rules. The efforts of dodol craftsmen and traders in maintaining the dodol business are (a) maintaining the quality of the dodol as seen from the taste that is still delicious, not moldy, and the cleanliness of the packaging, marketing the dodol through e-commerce, and producing and marketing the dodol themselves at their place of business, (b) selling dodol every day and placing markers at their place of business and providing other merchandise besides dodol at the dodol business place.